Experiences of employers, work colleagues, and mentors with new veterinary graduates and preferences towards new graduate support programmes. Issue 1 (2nd January 2021) - Gates, MC; McLachlan, I; Butler, S; Weston, JF
ABSTRACT: Aims: To describe the experiences of employers, work colleagues, and mentors who have recently worked with new veterinary graduates in New Zealand, explore factors influencing perceptions of new graduate performance, and identify opportunities for providing better support to new graduates and their employers. Methods: All veterinarians registered with the Veterinary Council of New Zealand (VCNZ) were invited to participate in a cross-sectional survey. Descriptive statistics were calculated for all study variables and a mixed-effects multivariable logistic regression model was constructed to explore factors associated with perceptions of new graduate performance. Thematic analysis was performed on free-text comments to identify key issues with new graduate support. Results: The survey was completed by 83 veterinarians with 68 (81.9%) providing information on 95 individual new graduates they had mentored. New graduates exceeded expectations in their ability to research cases and communicate with colleagues while time management and awareness of financial issues were highlighted as weaknesses. The mean total time respondents spent supervising new graduates during their first year was 166.8 (median 95; min 0; max 852) hours. New graduates who were not considered the best applicants for the job and those who had left their job were 6.3 (95% CI = 2.11–11.8) and 5.4 (95% CI = 1.55–19.0) times, respectively, more likely to be rated as performing below expectations. Thematic analysis revealed major themes related to the inadequate preparation of students in veterinary school, employers lacking adequate training and resources to supervise new graduates, and intergenerational differences in work ethic and expectations, which may be contributing to burnout and dissatisfaction for new graduates and their employers. Components of new graduate support programmes that were perceived to be most helpful were having regular meetings between the supervisor and employee to discuss performance and wellbeing, having compulsory sessions with an experienced veterinarian for career advice, and having non-compulsory checklists of technical and non-technical skills to guide professional development planning. However, there was varying levels of support for including these measures in a formal new graduate support programme. Conclusions: While respondents highlighted many challenges faced by new graduates and their employers, there was often disagreement about the root cause of the problem and potential solutions. Clinical relevance: Providing non-compulsory checklists to help employers work with new graduates to develop tailored professional development plans and support structures within their unique practice environment may result in more positive experiences as new graduates transition from student to independent practitioner.